Censorship as a Taboo during Political “Thaw” - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
During political “thaw”, in years 1955−1956 in the People’s Republic of Poland, it write in newspapers about themes banned earlier. One of such many theme formerly banned was censorship (Main Office of Control of Press, Publications and Shows). Journalists wrote about books banned by censorship, prohibited publications and black-listed writers, whose books had removed from libraries and destroyed. Situation is changed in 1958 – it is not allowed to write again about existence and activity of censorship